PENGARUH MEDIA MICROSOFT OFFICE SWAY UNTUK MENINGKATKAN MINAT BELAJAR SISWA - Sri Wulandari; Ahyar; Ita Fiitriati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Students’ learning interest is a crucial factor influencing the success of the learning process. The lack of variety in engaging learning media often becomes an obstacle in enhancing students’ interest in learning. This study aims to investigate the effect of implementing the “Microsoft Office Sway” media on improving students’ learning interest at SMPN 4 Bolo. The research employed an experimental method (True Experimental Design) with a Non-Equivalent Control Group Design, comparing a control group that used conventional learning methods with an experimental group that utilized Microsoft Office Sway media. The population of this study consisted of all eighth-grade students at SMPN 4 Bolo, totaling 67 students. The sample included two class groups: class VIII-2 as the experimental group and class VIII-3 as the control group, selected based on purposive sampling criteria. The criteria determined that the selected classes were considered representative of the population. To measure the influence of Sway media on students’ learning interest, the researchers used questionnaire instruments consisting of 25 items for the “Sway Media Implementation” questionnaire and 25 items for the “Learning Interest” questionnaire, analyzed using a Likert scale. Descriptive analysis was conducted to compare the mean scores from both questionnaires. Hypothesis testing was carried out using Simple Linear Regression analysis with Inferential Statistics through SPSS 21. Prior to hypothesis testing, prerequisite analyses, namely normality and homogeneity tests, were conducted to determine whether the null hypothesis (H0) would be rejected and the alternative hypothesis (Ha) accepted, or vice versa.